Fatty Acid Profile and Cholesterol Levels of Quail Eggs Fed with Kayambang Flour (Salvinia molesta D.S Mitchell) in Ration Based on Lemuru Fish Oil and Palm Oil Combination - S. N. Putri; D. M. Suci; W. Hermana (Jurnal Sain Peternakan Indonesia, 2022)
This study aimed to analyze the effect of adding a Salvinia molesta D.S Mitchell, sardinela longecips oil, and palm oil to profile fatty acid compotition of quail egg. This study used a complete randomized design (CRD) with 4 treatments and 5 replications. The ration contains 21% crude protein and 3000 kcal/kg metabolic energy. The treatment rations used consisted of control rations (without using Kayambang flour (P0) and treatment rations using 2%, 4% and 6% Kayambang meal on rations based on 4% lemuru fish oil and 2% palm oil (P2, P4 and P6) The results showed that the use  of Kayambang leaf meal at levels of 2%, 4% and 6% in a ration containing 4% lemuru fish oil and 2% palm oil increased total n-3 fatty acids, EPA and DHA in egg yolks ( P<0.05).  Egg yolk cholesterol tends to decrease with the use of Kayambang meals. It can be  concluded that the use of 2% and 4% Kayambang meal resulted in the ratio of n- 6 and n- 3 in egg yolks of 6.74:1 and 7.48: 1.